Aqueous Geochemical and Microbial Variation Across Discrete Depth Intervals in a Peridotite Aquifer Assessed Using a Packer System in the Samail Ophiolite, Oman. Issue 9 (8th September 2021) - Nothaft, Daniel B.; Templeton, Alexis S.; Boyd, Eric S.; Matter, Juerg M.; Stute, Martin; Paukert Vankeuren, Amelia N.; ,
Abstract: The potential for molecular hydrogen ( H 2 ) generated via serpentinization to fuel subsurface microbial ecosystems independent from photosynthesis has prompted biogeochemical investigations of serpentinization‐influenced fluids. However, investigations typically sample via surface seeps or open‐borehole pumping, which can mix chemically distinct waters from different depths. Depth‐indiscriminate sampling methods could thus hinder understanding of the spatial controls on nutrient availability for microbial life. To resolve distinct groundwaters in a low‐temperature serpentinizing environment, we deployed packers (tools that seal against borehole walls during pumping) in two 400 m ‐deep, peridotite‐hosted wells in the Samail Ophiolite, Oman. Isolation and pumping of discrete intervals as deep as 108 m to 132 m below ground level revealed multiple aquifers that ranged in pH from 8 to 11. Chemical analyses and 16S rRNA gene sequencing of deep, highly reacted Ca 2 + − OH − groundwaters bearing up to 4.05 μ mol ⋅ L − 1 H 2, 3.81 μ mol ⋅ L − 1 methane ( C H 4 ) and 946 μ mol ⋅ L − 1 sulfate ( S O 4 2 − ) revealed an ecosystem dominated by Bacteria affiliated with the class Thermodesulfovibrionia, a group of chemolithoheterotrophs supported by H 2 oxidation coupled to S O 4 2 − reduction. In shallower, oxidized Mg 2 + − HCO 3 − groundwaters, aerobic and denitrifying heterotrophs were relatively more abundant. High δ 13 C and δ D of C H 4 (up to 23.9 ‰ VPDB and 45 ‰ VSMOW, respectively) indicated microbial C H 4 oxidation, particularly in Ca 2 + − OH − waters with evidence of mixing with Mg 2 + − HCO 3 − waters. This study demonstrates the power of spatially resolving groundwaters to probe their distinct geochemical conditions and chemosynthetic communities. Such information will help improve predictions of where microbial activity in fractured rock ecosystems might occur, including beyond Earth. Plain Language Summary: Peridotite rocks can react with water to form hydrogen gas. Microbes can combine hydrogen with oxidants to power their cells. Rocks similar to peridotite have been abundant throughout the history of Earth and the Solar System. Therefore, peridotite‐water interaction is important for understanding the history and distribution of life. Prior studies investigating these processes have sampled waters from the surface of peridotite exposures or from open wells. These sampling methods risk contaminating deep, peridotite‐hosted waters with shallower waters influenced by the atmosphere. In this study, we used packers (tools that can be used to pump waters from separate regions of the subsurface in isolation) to better understand the distribution of microbes and nutrients in subsurface peridotites. We sampled waters from separate subsurface zones as deep as 108–132 m in two wells in peridotite. Waters from different depths had distinct chemical compositions and microbial communities. Sulfate reducing bacteria were dominant in waters that had most extensively reacted with peridotite in isolation, while microbes that consume nitrate or oxygen were also prevalent in waters with more evidence of atmospheric influence. The advanced sampling techniques we used help to distinguish where and how microbes live in the subsurface. Key Points: Packers were used to sample groundwaters from discrete peridotite aquifers The discrete aquifers contained waters with distinct chemical compositions and microbial communities Chemolithoheterotrophic sulfate reduction was a dominant metabolic strategy inferred from 16S rRNA gene homology in highly reacted fluids